Age-related decline of dopamine synthesis in the living human brain measured by positron emission tomography with l-[β- 11C]DOPA - Ota, Miho; Yasuno, Fumihiko; Ito, Hiroshi; Seki, Chie; Nozaki, Shoko; Asada, Takashi; Suhara, Tetsuya (Life sciences (1973), 2006)
Loss of dopamine synthesis in the striatum with normal human aging has been observed in the postmortem brain. To investigate whether there is age-associated change in dopamine synthesis in the extrastriatal brain regions similar to that in the striatum, positron emission tomography studies with 11C-labelled l-DOPA were performed on 21 normal healthy male subjects (age range 20–67 years). Decline in the tissue fraction of gray matter per region of interest was also investigated. The overall uptake rate constant for each region of interest was quantified by the Patlak plot method using the occipital cortex as reference region. Regions of interest were set on the dorsolateral prefrontal cortex, lateral temporal cortex, medial temporal cortex, occipital cortex, parietal cortex, anterior cingulate, thalamus, midbrain, caudate nucleus, and putamen. Test–retest analysis indicated good reproducibility of the overall uptake rate constant. Significant age-related declines of dopamine synthesis were observed in the striatum and extrastriatal regions except midbrain. The decline in the overall uptake rate constant was more prominent than in the tissue fraction of gray matter. These results indicate that the previously demonstrated age-related decline in striatal dopamine synthesis extends to several extrastriatal regions in normal human brain.